MONITORING ON PLANT LEAF WATER POTENTIAL USING NIR SPECTROSCOPY FOR WATER STRESS MANAGEMENT - Diding Suhandy (Jurnal Teknologi & Industri Hasil Pertanian, 2008)
The performance of the calibration model with temperature compensation for on-plant leaf water potential (LWP) determination in tomato plants was evaluated. During a cycle of water stress, the on-plant LWP measurement was conducted. The result showed that the LWP values under water stress and recovery from water stress could be monitored well. It showed that a real time monitoring of the LWP values using NIR spectroscopy could be possible.   Keywords: water stress, real time monitoring of leaf water potential, NIR spectroscopy, plant response-based